Preschoolers’ true and false reports: Comparing effects of the Sequential Interview and NICHD protocol - Magnusson, Mikaela (Legal and criminological psychology, 2021)
Purpose The current study aimed to examine a Norwegian technique for conducting investigative interviews with preschoolers: the Sequential Interview (SI). The SI advocates for increased initial rapport building and includes a pre-determined break before the substantive phase. To explore the potential benefits and risks of the SI, the technique was compared with an adapted version of the National Institute of Child Health and Development (NICHD) protocol. Methods A total of 129 preschoolers (3–6 years) were interviewed with either the SI or NICHD protocol about a self-experienced (Exp. I) or non-experienced (Exp. II) event. Result For Exp. I, no significant difference was observed across interview conditions in the number of reported details about a self-experienced event. Children interviewed with the SI exhibited a slightly lower accuracy rate compared to those interviewed with the NICHD protocol. For Exp. II, a total of 31.1% of the preschoolers initially assented to remembering a fictive (false) experience and 15.6% gave an account (>40 details) of the non-experienced event. We found no difference between interviewing conditions in assent rates or number of false accounts. Conclusions The study provides valuable insights into the difficulties involved when interviewing young children. The results showed few differences between the novel SI model and the well-established NICHD protocol. While many preschoolers could provide accurate testimony, some embedded worrisome false details in their narratives. Furthermore, a minority of children gave false reports about non-experienced events when interviewed with the two techniques. Methodological limitations and suggestions for future research will be discussed.